Neuroprotective Effects of Human Umbilical Cord-Derived Mesenchymal Stem Cells From Different Donors on Spinal Cord Injury in Mice - Zhu, Xu; Wang, Zhen; Sun, Yi Eve; Liu, Yuchen; Wu, Zhourui; Ma, Bei; Cheng, Liming (Frontiers in Cellular Neuroscience, 2022)
Spinal cord injury (SCI) is caused by an external force, leading to severe dysfunction of the limbs below the injured segment. The inflammatory response plays a vital role in the prognosis of SCI. Human umbilical cord mesenchymal stem cell (hUCMSC) transplantation can promote repair of SCI by reducing the inflammatory response. We previously showed that hUCMSCs from 31 donors had different inhibitory abilities on BV2 cell proliferation. In this study, three experimental groups were established and the mice were injected with different lines of hUCMSC. Hind limb motor function, Hematoxylin-eosin (HE) staining, immunohistochemistry, Western blot, qRT-PCR and RNA sequencing and correlation analysis were used to investigate the effects of hUCMSC transplantation on SCI mice and the underlying mechanisms. The results showed that the therapeutic effects of the three hUCMSC lines were positively correlated with their inhibitory abilities of BV2 cell proliferation rates in vitro. The MSC_A line had better therapeutic effect on improving hind limb motor function and greater effect on reducing the expression of Gfap and Iba1 and increasing the expression of NeuN. Differentially expressed genes including Zbtb16, Per3 and Hif3a were probably the key genes involved in the protective mechanism by MSC_A after nerve injury. QRT-PCR results further verified that Zbtb16, Per3 and Hif3a expressions reduced by SCI, could be reversed by MSC_A application. These results suggest that the effect of HUCMSCs transplantation on acute SCI depends on their inhibitory abilities to inflammation reaction after nerve injury, which may help to shape future use of hUCMSCs combined with improving the effectiveness of clinical transformation.